Screening and Isolation of Cytotoxic Compounds From Local Marine Aaptos Species - Kee, Cheng Ling (2006)
Over the recent years, marine sponges have been the target of research as a source of new chemicals with therapeutic potential. They have been proven to have a high strike rate especially for cytotoxic compounds. Thirteen species of marine sponges collected from Pulau Kapas, Pulau Bidong and Pulau Redang were preliminarily identified as Aaptos sp. (I), Xestospongia exigua (2), unidentified sp. (3), Xestospongia sp. (4), Xestospongia testudinaria (5), Callyspongia sp. (6), Theonella sp. (7), Theonella sp. (S), Sigmaducza arnbolnenuris (9), Ircinia sp. (lo), Dysedza sp. (1 I), unidentified sp. (12) and Ircinia Halisarca (13). The crude methanol extracts of these samples were screened for cytotoxic activities against a panel of cell lines, namely HL-60 (promyelocytic leukemia), CEM-SS (T-lymphoblastic leukemia), MCF-7 (breast cancer), HeLa (cervical cancer), HT-29 (colon cancer) and L929 (murine fibrosarcoma from mouse) using a colorimetric tetrmlium (MTT) assay. Crude extracts from 1 and 10 were active against all six cell lines with CDm values ranging from 1.05 to 24.1 pglml whereas extracts 2, 3 and 8 showed activity only against H1L-60, CEM-SS and HT-29 with CDso values ranpg from 12.95 to 29.5 pglml. Aaptos sp. (1) was chosen for further investigations due to its abundance and strong cytotoxic activity. Bioassay guided isolation and purification of compounds afforded three cytotoxic alkaloids. H19 was identified as the previously isolated aaptamine [I] and the two orange compounds were established as the new aaptaminoid alkaloids, 01 and 02. All three compounds exhibited significant cytotoxic activity against CEM-SS cells with respective CD50 values of 15.0,5.3 and 6.7 pg/ml. When tested against 3T3 (normal mouse fibroblast), all three compounds displayed weak cytotoxicities. The CDS0 of compound 01 and 02 were determined as 21.2 and 21.0 pg/ml respectively. On the other hand, compound 3319 did not achieve a CDSo. Phase contrast microscopic analysis showed that compound H19, 01 and 02 induced apoptosis in CEM-SS cells. The apoptotic features observed include cell shrinkage, condensation of chromatin material, membrane blebbing and the formation of apoptotic bodies. Due to insufficient quantity of 0 1 and 02, only H19 was subjected to subsequent evaluation using fluorescence microscopy. These results further supported that H19 induce apoptosis in CEM-SS as exemplified by the morphological changes observed.